Multimodal Evaluation of Patients with Acute Posterior Multifocal Placoid Pigment Epitheliopathy and Serpiginous Choroiditis. (17th November 2018) - Mangeon, Monique; Zett, Claudio; Amaral, Camila; Novais, Eduardo; Muccioli, Cristina; Andrade, Gabriel; Nascimento, Heloisa; Belfort, Rubens
ABSTRACT: Purpose : To evaluate retinal and choroidal changes in patients with non-granulomatous choroiditis using the multimodality imaging (MMI). Methods : Eight eyes of four patients were analyzed. Three patients (six eyes) were diagnosed with serpiginous choroiditis (SC) and one patient (two eyes) with acute posterior multifocal placoid pigment epitheliopathy (APMPPE). The patients were imaged on the same day using the RTVue Avanti XR instrument OCT/OCTA (Optovue Inc, Fremont, CA), Heidelberg Retina Angiograph 2 FAF and FA (Heidelberg Engineering, Germany), and TRC50DXi Topcon FP (Topcon Medical Systems, Oakland, NJ). Results : OCT angiography (OCTA) showed hypoperfusion in all the cases, reperfusion in choriocapillaris in two eyes after treatment and identified a choroidal neovascularization (CNV), which was not detected on the fluorescein angiography (FA). Conclusions : OCTA may be an effective noninvasive image modality to follow up these patients and may provide further information to help us to understand the pathophysiology and complications of these diseases.